2017
DOI: 10.1002/14651858.cd012890
|View full text |Cite
|
Sign up to set email alerts
|

EEG neurofeedback for executive functions in children with neurodevelopmental challenges

Abstract: EEG neurofeedback for executive functions in children with neurodevelopmental challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…Given the close associations between EF, processing speed, and intelligence (M. Anderson, 1992Anderson, , 20012017), recent research has examined the possibility of training EFs, particularly working memory, in an attempt to increase gF (e.g., Jaeggi, Buschkuehl, Jonides, & Perrig, 2008). Alternatively, investigating the effectiveness of neurofeedback training in this group could be of benefit (Landes et al, 2017). Although processing speed is likely to be a biological constraint that is 'untrainable', EFs are likely to be subject to training a developmental change.…”
Section: Discussionmentioning
confidence: 99%
“…Given the close associations between EF, processing speed, and intelligence (M. Anderson, 1992Anderson, , 20012017), recent research has examined the possibility of training EFs, particularly working memory, in an attempt to increase gF (e.g., Jaeggi, Buschkuehl, Jonides, & Perrig, 2008). Alternatively, investigating the effectiveness of neurofeedback training in this group could be of benefit (Landes et al, 2017). Although processing speed is likely to be a biological constraint that is 'untrainable', EFs are likely to be subject to training a developmental change.…”
Section: Discussionmentioning
confidence: 99%
“…The technology provides bipolar asymmetry training, during which regulates the distribution of frequencies of different intensity. For example, multidirectional changes in the relative EEG intensity in the brain hemispheres can cause enhancement of cognitive activity and attention processes (Putman, 2005), as well as improvement of executive functions (Kim et al, 2013;Landes et al, 2017). Studies have shown that the effectiveness of biofeedback is determined by many factors such as: motivation (Kleinman, 1981;Saho & Harano, 1984), training (Keefe & Gardner, 1979), respiration (Conde Pastor et al, 2008), and some individual characteristics (Suter, 1979;Li et al, 2019).…”
Section: Biofeedbackmentioning
confidence: 99%
“…29 Search terms for childhood-onset disabilities, including neurodevelopmental disorders, were derived from a combination of search terms from a previous systematic review on vocational interventions for young adults with childhood-onset disabilities, 51 the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, 38 the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, 52 and a Cochrane systematic review on neurodevelopmental disorders. 53 The search strategy for Medline can be found in the Supplemental Information. Additional articles were identified by scanning the reference lists of included studies.…”
Section: Search Strategy and Information Sourcesmentioning
confidence: 99%